استنطاق الموروث الثقافي الحساني، قراءة في نوازل وأحكام ورسائل القاضي محمد يحيظه بن عبد الباقي (ت1370هـ) Reading in the Judge Mohamad Yehdih Interrogating the Hassani Cultural Heritage:.bin Abdul Baqi's Nawazil, Judgements and Letters (مجلة إحالات, 2026)
إن النوازل والفتاوى والأحكام الفقهية ليست مجرد أراء ذهنية افتراضية وجهت إلى الفقيه ليجيب عنها بما لاح له نظره، وإنما هي أسئلة واقعية حدثت حقيقة دون تحريف مقصود، بل هي تعبير عن اشكالات وتساؤلات شغلت هموم الناس اليومية. وبالعودة لهذه النصوص نرصد تميز محتواها وما تقدمه من معطيات غطت حيزا في غاية الأهمية من الحياة الثقافية للمجتمع البيظاني بمجاليه الحضاري والبدوي. لذلك يسعى هذا البحث إلى لفت الانتباه لأهمية النوازل والأحكام في إعادة صياغة وكتابة البحث التاريخي، باعتبارها موردا من مصادر التحقيب، وذلك لما تكتسيه هذه الوثائق من أهمية بالغة في جمع واحتواء الموروث الثقافي الحساني وبمثابة وعاء حفظ ذاكرة أهل الصحراء الاجتماعية والاقتصادية والفكرية في فترة من الفترات، كما يروم هذا البحث إلى استنطاق النوازل باعتبارها مخزون حضاري، وموروث ثقافي محايد، يرجى مساءلته، ثم استثماره والافادة والنهل من ماضيه، كونه الشاهد الحي على محطات تاريخية عدة، فاخترت للوقوف على هذا الموروث الثقافي، مجموعة من النوازل والأحكام والرسائل، ترجع للمفتي والقاضي الجليل محمد يحظيه بن عبد الباقي ت1370هــ/1949م.Abstract: Al-Nawazil, Fatwas, and the juristic judgements are not only hypothetical views that have been addressed to the jurist to answer them, but also real questions occurred without deliberate distortion. They are expressions of problems, and issues that have preoccupied the daily concerns of people. Going back to these texts, we observe the distinctiveness of content and data that covered a very important part of the cultural life of El-Bithan community in both, cultural and Bedouin fields. This research wherefore seeks to draw attention to the significance of juristic judgements, and Al-Nawazil in reformulating and writing the historical research, as one of the most salient sources of excavation, because these documents would better help in collecting and saving the Hassani cultural heritage, which is considered a container for preserving the social, economic and intellectual memory of the people of Sahara in a certain period of time. This research also aims to examine Al-Nawazil as a civilizational stock and a neutral cultural heritage, which requires questioning, investing it, and then benefiting from its past, as it is the living witness to several historical phases, so I chosen to find out this cultural heritage, hinging on a set of Nawazil, judgements and messages, ascribed to the highly esteemed Judge Mohamad Yehdih bin Abdul Baqi 1370 AH / 1949 AD.